Effect of 30 Minutes Walking on Blood Pressure of Elderly in Paccerakkang District of Makassar - Andi Nurfadilah Rezky; Nurmiyanti Nur; Rismawati Samad; Arnis Puspitha (Universitas Hasanuddin, 2019)
Background: Sports activity affects a person's fitness level. Sports activities in the form of aerobic exercise, resistance or resistance training and flexibility exercises can improve your fitness. The exercise was done with medium intensity 3 times per week and 30 minutes duration. The importance of one's body fitness should get more attention. Especially in improving the quality of physical condition capabilities such as cardiovascular endurance, muscle strength and endurance, body shape. In this case a person can perform maximum exercise on the physical condition. This study aims to find out how the effect of walking 30 minutes to decrease blood pressure in elderly in working area of Health Center of Pacer Balik Kota Makassar. Method: This research is Quasy Experiment with Pre and Post Test Without Control design. The sample of research is 30 respondents. The research instrument is a tool to check uric acid levels and blood pressure measuring devices. Result: Blood pressure of respondent before walking done have mean value 3,40 mmHg and walking done have mean value 2,47 mmHg, Based on hypothesis test which have been done, hence obtained conclusion that walking 30 min influence significantly to pressure drop blood. Based on the calculation that has been done, obtained p-value for the pair of pre-posttest variable for blood pressure is 0.000 while the significance level α = 0.05. Conclusion and Suggestion: Based on hypothesis testing that has been done, hence obtained conclusion that walk 30 minutes influence significantly to decrease blood pressure. By knowing the influence of elderly gymnastics on the decrease of blood pressure in elderly with hypertension, nurses are expected to give and suggest non-pharmacological intervention and walk 3 times a week with 30 minutes duration in minimizing risk of complication of hypertension.